Evaluation of Internal Control Efficiency Based on COSO Framework: A Case Study of Finance Division of Mueangkao Municipality, Khon kaen Province - Pattanawongchaikul, Chotiarpha; Aungvaravong, Chuenjit (RMUTL Journal of Business Administration and Liberal Arts, 2017)
This study was aimed to the assessment of efficiency of Internal control based on COSO framework: A case study of finance division of Mueangkao Municipality, Khon kaen Province. The concept of COSO comprises of five elements; Control environmental, Risk assessment, Control activities, Information and communication and Monitoring. The samples used for this study consisted of twenty-six participants nominated from five Divisions within the organization; Finance management, Statistic finance, Development revenue and Revenue collection, Taxation mapping and property registration and General Administration and Procurement. The questionnaires used as an instrument for the data collection were separated into three parts as follows; 1. Personal information of the participants. 2. Participant’s opinion about the internal control system of finance division of each divisions based on COSO framework as described above. 3. The additional suggestion or recommendation from the participants over this management system for further development. The statistic used for data analysis was included Frequency, Percentage, Mean, Standard and Deviation. As the result of this study, it could be concluded into three points as follows; 1. In overall, based on COSO framework, the level of efficiency of the internal control system of finance division is average; the information and communication and control activities are in the highest level compared with the others. 2. Should considers on five divisions separately, it was found that the Development of revenue and revenue collection and Taxation mapping and property registration are the highest efficiency, meanwhile the rest is only in average level. 3. Based on this study, it is recommended that the Director or Manager of each division should have the proper policy or new standard to be used for managing and developing of their internal control system, especially the division of General of Administration and Procurement, Finance management and Statistic finance respectively. This is to improve the quality and efficiency of the public finance management system in the future.